Phylogenetic analysis of local Papuan (Indonesia) sweet potato genotypes using the maturase K (matK) molecular marker - NOUKE L. MAWIKERE; SARASWATI PRABAWARDANI; ANTONIUS SUPARNO; SARTJI TABERIMA; NAHOR OLLUDIUM; AGUSTINUS WARBAAL; ZARIMA WIBAWATI; LULUT DWI SULISTYANINGSIH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Mawikere NL, Prabawardani S, Suparno A, Taberima S, Olludium N, Warbaal A, Wibawati Z, Sulistyaningsih LD. 2025. Phylogenetic analysis of local Papuan (Indonesia) sweet potato genotypes using the maturase K (matK) molecular marker. Biodiversitas 26: 1367-1375. This study aimed to investigate the genetic relationship among 12 local Papuan sweet potato genotypes using the maturase K (matK) molecular marker. DNA was extracted from fresh leaf samples and amplified using the matK primer, with sequencing conducted through the Sanger method. Sequence analysis was performed using MEGA11 software, employing BLAST for alignment with GenBank data. Clustering analysis was performed using the neighbor-joining method. While, the phylogenetic tree was constructed using Maximum Likelihood analysis with 1,000 bootstrap replications. The study showed extensive morphological diversity among the sweet potato genotypes, except for L-MKW and Biak-1 genotypes. Nucleotide variation ranges from 858 bp to 867 bp, with polymorphic sites identified at key nucleotide positions. Sweet potato genotype with the largest number of nucleotides was Numfor (867 bp). There were 12 polymorphic sites in nucleotide sequences 1-8, 837, 838, 864, and 865. The average nucleotide composition of twelve sweet potato genotypes was T/U (28.34%), C (15.76%), A (38.01%), and G (17.89%). The number of amino acids formed varied from 265 (Nabire) to 271 (Prafi-1, Mokwam), with an average number of 267.58. The highest amino acid composition was Lysine (Lys/K) 11.87%. Only four sites had polymorphic amino acids in the amino acid sequences 1, 2, 3, and 280. The grouping pattern of Papuan sweet potato genotypes based on nucleotide similarities amplified by the matK primer formed three groups based on their nucleotide similarities, namely i) Mokwam, Numfor, L-MKW; ii) Airani Serui, Prafi, Nabire; and iii) Ungu MKW, L-Sorong, Koya-4, Tinta-1, Biak-1, Amban Pantai-2. This cluster highlights the genetic diversity within Papuan sweet potato populations. Phylogenetic analysis revealed a close relationship between the studied genotypes and other species of the Ipomoea genus. These findings provide valuable insights into the genetic diversity of Papuan sweet potatoes, offering potential applications for conservation and local crop improvement efforts.